(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Аннотация: Особое внимание уделено общей характеристике, экологическому значению и эволюционному месту херамид. Подробно освещены их классификация, главный представитель - Chara vulgaris, а также способы размножения, в том числе вегетативный и половой. Также отмечена роль земноводных в экологии водоемов и их значение как биоиндикатора. Abstract: Special attention is paid to the general characteristics, ecological importance and evolutionary place of cheramids. Their classification, main representative - Chara vulgaris, and methods of reproduction, including vegetative and sexual reproduction processes, are covered in detail. The role of amphibians in the ecology of water bodies and their importance as a bioindicator is also noted.